Prevalence and Associated Risk Factors of COVID-19 Infection Among Healthcare Workers in a Pandemic Hospital - Ramazan Korkusuz (Galenos Yayinevi, 2021)
Introduction:This study aimed to investigate the prevalence of Coronavirus disease-2019 (COVID-19) infection among healthcare workers in our hospital with the risk factors affecting the transmission and course of the disease and to determine the control measures.Methods:Medical records of healthcare workers diagnosed with COVID-19, confirmed by polymerase chain reaction (PCR) between 11 March and 30 April 2020, were retrospectively analyzed in our hospital in the center of İstanbul, the city with the highest number of cases in our country. Realtime PCR detection was used to verify the diagnosis of the healthcare workers. A rapid diagnostic test kit for COVID-19 immunoglobulin M (IgM) and IgG antibodies was used in seroconversion analysis.Results:In our hospital, 4,177 COVID-19 cases confirmed by the laboratory between March 11 and April 30 2020 were followed. Of the 4177 cases, 165 (3.95%) were healthcare workers. The majority of healthcare workers with positive test results were nurses (36.3%), and 118 (71.5%) of the healthcare workers worked 40 h or more per week. Thoracic tomography examinations were performed in all infected healthcare workers, and 69 (41.8%) were diagnosed with pneumonia by the detection of ground patchy lesions.Conclusion:During the epidemic, early training of healthcare workers on the disease, use of personal protective equipment, and infection control are extremely important to reduce the risk of infection among healthcare workers. Periodic screening of asymptomatic healthcare workers can also help protect patients and hospital staff and prevent loss of workforce.